PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. HEXINDO ADIPERKASA - Kartika Dwi Astuti; Amanda Setiorini (Jurnal Manajemen Bisnis Krisnadwipayana, 2020)
This study aims to analyze the effect of competence and work environment on employee performance at PT. Hexindo Adiperkasa Tbk. This is a quantitative descriptive study using primary data by giving questionnaires to employees of PT. Hexindo Adiperkasa Tbk, located in the Pulo Gadung Industrial Estate, Jakarta, discussed on Jl. Goat Island II Kav.I-II.No.33. From a population of 1,500 employees, a total sample of 94 respondents was obtained using the Slovin formula. The technique used to take samples is the random sampling method and the type of data used is heterogeneous. The analytical tool used in this study is multiple linear regression. The results show there is a positive and significant effect simultaneously between competence and work environment on employee performance. Partially, competence has a significant influence on employee performance, as well as work environment variables.